THE LEGACY OF ‘MALLABHUM’ WEAVING ART - Malay Ghosh (International Engineering Journal For Research & Development, 2022)
“Every weaver hashis/her own dream to weave”—This quote justified that weaving includes personal feeling. Hence it stands apart from all other industries all over India. It is a kind of art which involves both the creative power as well as physical power. The cultural heritage and ancient history of India are weaved actually in Handloom or ‘Tant. India is the country where women adorned themselves with sharee, the most beautiful product of Handloom. After two repetitive years of pandemic lets discuss the present scenario of this handloom art specially in rural areas like ‘Mallabbum’ areas (i.e Sonamukhi and Bishnupur). Handlooms are the warp and weft of India. our culture and aesthetics are rooted nowhere but in its threads. Each fabric tells us a new kind of story; the original one.